1982
DOI: 10.1104/pp.69.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence Homology Exists between the Chloroplast and Nuclear Ribosomal DNAs of Euglena gracilis

Abstract: The nuclear and chioroplast ribosomal DNAs from Eugkna were shown to have specific regions of nucleotide sequence homology. The regions of homology were identified by hybriization ofrestriction endonuclease DNA fragments of cloned chloroplast and nuclear ribosomal DNAs to one another. The regions of homolo between these two ribosomal DNAs were In that part of the genes that code for the 3' end of the small rRNAs (16S and 19S) and near or at the DNA sequences coding for the 5S RNAs.The nucleotde sequence homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In addition, a 2,300 nucleotide RNA hybridizes faintly with the probe from the 16S rRNA gene. This results most likely from hybridization to the cytoplasmic small subunit rRNA, which is 2,305 nucleotides in length (Sogin et al 1986) and has been shown to hybridize with the chloroplast 16S gene on Southern blots (Curtis and Rawson 1982). The 2,300 nucleotide band was not seen in Northern blots of RNA from isolated chloroplasts (McGarvey 1988).…”
Section: Analysis Of Rrn Transcription Using Northern Blot Hybridizationmentioning
confidence: 96%
“…In addition, a 2,300 nucleotide RNA hybridizes faintly with the probe from the 16S rRNA gene. This results most likely from hybridization to the cytoplasmic small subunit rRNA, which is 2,305 nucleotides in length (Sogin et al 1986) and has been shown to hybridize with the chloroplast 16S gene on Southern blots (Curtis and Rawson 1982). The 2,300 nucleotide band was not seen in Northern blots of RNA from isolated chloroplasts (McGarvey 1988).…”
Section: Analysis Of Rrn Transcription Using Northern Blot Hybridizationmentioning
confidence: 96%